Kebijakan Ekonomi Proteksi dalam Meningkatkan Kemandirian Ekonomi dan Kesejahteraan Pondok Pesantren Gontor 3 - mohammadnur irfan; Aunur Rofiq; Umrotul Khasanah; Bima FandiAsy’arie (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study aims to analyze the economic protection policy in increasing the economic independence and welfare of Gontor 3 Islamic Boarding School. The study uses a descriptive qualitative approach with a case study type. Data were obtained through observation, interviews, and documentation of student care, business unit managers, administration, ustadz, and students. Data analysis uses the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the economic protection policy is implemented through restrictions on external economic activities and fulfilling the needs of students through internal business units of the Islamic boarding school such as student cooperatives, Latansa Mart, laundry, and other production units. This policy is able to create a stable internal economic cycle, strengthen the economic independence of the Islamic boarding school, and improve the welfare of the Islamic boarding school through subsidies for student needs, development of educational facilities, health services, and teacher welfare. The research findings also show that the implementation of the economic protection in Gontor 3 is relevant to Friedrich List's protectionism theory and is in line with the principles of Islamic welfare based on maqāṣid shari'ah.